A suburban sediment budget: Coarse‐grained sediment flux through hillslopes, stormwater systems and streams. Issue 13 (30th July 2019) - Russell, Kathryn L.; Vietz, Geoff J.; Fletcher, Tim D.
Abstract: Sediment in urban stormwater systems creates a significant maintenance burden, while a lack of coarse‐grained bed sediment in streams limits their ecological value and geomorphic resilience. Gravel substrates, for example, provide benthic habitat yet are often scoured from the channel bed only to end up in a detention basin or treatment wetland. This dual problem of both 'too much' and 'too little' coarse‐grained sediment reflects a watershed sediment budget that is profoundly altered. We developed a conceptual urban coarse‐grained (>0.5 mm) sediment budget across three domains: hillslopes (urban land surfaces), the built stormwater network and stream channels. We then quantified key sources, sinks and storages for a suburban case study, using a combination of hillslope and in‐channel monitoring, and interrogation of local government records. Around 36% of the sediment supplied to the stormwater network reached the catchment outlet, a level of sediment delivery much higher than observed in similar‐sized natural catchments. The remainder was deposited in the sediment cascade and either stored, or extracted and removed from the catchment (e.g. material deposited in sediment ponds and gross pollutant traps). Conventional urban drainage networks are characterized by high hillslope sediment supply and low storage, resulting in efficient sediment delivery. Channel erosion, deposition in (and extraction from) pipes and channels, and floodplain deposition are small compared to sediment transport through the cascade. An understanding of the sediment budget of urban headwater catchments can provide stormwater and waterway managers with the information they need to address specific sediment problems such as sedimentation in stormwater assets and geomorphic recovery of urban streams. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : Erosion and sedimentation problems in urban stream systems indicate a highly altered sediment regime. A coarse‐grained sediment budget for a suburban headwater catchment revealed higher sediment delivery efficiency driving higher bedload yield in streams. Sediment is readily mobilized from urban catchments through stormwater drainage systems to streams and is captured in localized structures such as stormwater assets and weirs.